N-terminal domain of vacuolar SNARE Vam7p promotes trans-SNARE complex assembly - Xu, Hao (National Academy of Sciences, 2012)
SNARE-dependent membrane fusion in eukaryotic cells requires that the heptad-repeat SNARE domains from R- and Q-SNAREs, anchored to apposed membranes, assemble into four-helix coiled-coil bundles. In addition to their SNARE and transmembrane domains, most SNAREs have N-terminal domains (N-domains), although their functions are unclear. The N-domain of the yeast vacuolar Qc-SNARE Vam7p is a binding partner for the homotypic fusion and vacuole protein sorting complex (a master regulator of vacuole fusion) and has Phox homology, providing a phosphatidylinositol 3-phosphate (PI3P)-specific membrane anchor. We now report that this Vam7p N-domain has yet another role, one that does not depend on its physical connection to the Vam7p SNARE domain. By attaching a transmembrane anchor to the C terminus of Vam7p to create Vam7tm, we bypass the requirement for the N-domain to anchor Vam7tm to reconstituted proteoliposomes. The N-domain of Vam7tm is indispensible for trans-SNARE complex assembly in SNARE-only reactions. Introducing Vam7(1-125)p as a separate recombinant protein suppresses the defect caused by N-domain deletion from Vam7tm, demonstrating that the function of this N-domain is not constrained to covalent attachment to Vam7p. The Vam7p N-domain catalyzes the docking of apposed membranes by promoting transinteractions between R- and Q-SNAREs. This function of the Vam7p N-domain depends on the presence of PI3P and its affinity for PI3P. Added N-domain can even promote SNARE complex assembly when Vam7 still bears its own N-domain.